The Use of Social Media to Increase Sales Profits - Nensa Widiawati Sukma; Romla Fibrianti; Adiba Maulidiyah (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2026)
This study aims to analyze the role of social media in increasing sales profits among Micro, Small, and Medium Enterprises (MSMEs). The research employs a qualitative method using a literature review and observation approach to collect data from various relevant sources. The findings indicate that the utilization of social media as part of digital marketing has a positive impact on increasing product sales. Social media enables business owners to reach a wider audience, disseminate product information more quickly, enhance customer interaction and trust, and conduct promotional activities at relatively low costs. Platforms such as Instagram, Facebook, TikTok, and various e-commerce marketplaces have proven effective in expanding market reach and increasing sales volume. Furthermore, digital features such as visual content, customer testimonials, and online promotions significantly influence consumers' purchasing intentions. However, several challenges remain, including intense market competition, changes in social media algorithms, limited resources, and insufficient skills in managing digital content. Therefore, optimizing social media utilization and improving digital competencies are essential factors in supporting marketing success and increasing business profitability.